The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0274509
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 reinfections during the first three major COVID-19 waves in Bulgaria

Abstract: Background The COVID-19 pandemic has had a devastating impact on the world over the past two years (2020-2021). One of the key questions about its future trajectory is the protection from subsequent infections and disease conferred by a previous infection, as the SARS-CoV-2 virus belongs to the coronaviruses, a group of viruses the members of which are known for their ability to reinfect convalescent individuals. Bulgaria, with high rates of previous infections combined with low vaccination rates and an elderl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 184 publications
0
10
0
Order By: Relevance
“…As the data related to SARS-CoV-2 reinfection becomes more available, sub-analyses could be explored to examine the rates of reinfection by a variety of covariates, such as age, sex, comorbidities and history of vaccination. The results from this meta-analysis may serve as a comparison to future research on the risk of reinfection of Omicron and new emerging variants among the widely vaccinated population 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…As the data related to SARS-CoV-2 reinfection becomes more available, sub-analyses could be explored to examine the rates of reinfection by a variety of covariates, such as age, sex, comorbidities and history of vaccination. The results from this meta-analysis may serve as a comparison to future research on the risk of reinfection of Omicron and new emerging variants among the widely vaccinated population 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…First, a majority of the population must have been infected by that point (other-wise the IFR in Bulgaria would have to exceed 2%, which is unlikely), although how many exactly have been infected is not possible to say in the absence of an anti-nucleocapside serosurvey (and even then, seroreversion would probaly bias estimates downwards). Second, reinfections became an increasingly common phenomenon, first with the arrival of the Delta variant 38 , and especially after the appearance of Omicron. Third, the virulence of SARS-CoV-2 prior to Omicron was increasing, with the Alpha variant being more severe than the WT and the Delta variant being even more severe than Alpha; meanwhile the IFR estimates from 2020 and early 2021 were based on the WT virus.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, COVID- 19 has not yet been globally eliminated and experienced multiple waves of variants [31][32][33][34][35][36][37][38][39]. The proposed method partially incorporated the uncertainty of imputed cases, the heterogeneity of transmission dynamics, and the uncertainty of the growth rate estimates through the channels of sliding windows, data distribution, generation intervals, and reporting rates.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies found that non-compulsory measures reduced population mobility using mobile-phone data in Tokyo [8,34]. The survey conducted in Bulgaria implied that prior records of infections could confer certain levels of immunity protection, implicitly yielding an impact on the trajectory of later reinfection [35]. Second, other exterior driving factors may be playing roles as well, such as policies, environmental scenarios, urban space features, and potential interactions [36].…”
Section: Limitationsmentioning
confidence: 99%